2005
DOI: 10.1111/j.1365-2591.2005.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the renewal of calcium hydroxide paste on the apexification and periapical healing of teeth with incomplete root formation

Abstract: Replacement of calcium hydroxide paste was not necessary for apexification to occur, however, it did reduce significantly the intensity of the inflammatory process. Monthly renewal of calcium hydroxide paste reduced significantly the occurrence of apexification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 12 publications
4
51
0
4
Order By: Relevance
“…Due to wide apical foramen diameter and the presence of exudate in the periapical region, dressing dissolution rate increases, thereby creating the need for change. 21,22 The present study agrees with the following authors when suggesting to keep intracanal dressing inside the root canal for much longer periods without periodic changes: Chosack et al, 23 Felippe et al, 28 Steiner et al, 29 Chawla et al 33 and Túrkún. 36 The study conducted by Chawla 33 found mineralized tissue formation after intracanal dressing remained in the root canal for 6 to 12 months without periodic changes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Due to wide apical foramen diameter and the presence of exudate in the periapical region, dressing dissolution rate increases, thereby creating the need for change. 21,22 The present study agrees with the following authors when suggesting to keep intracanal dressing inside the root canal for much longer periods without periodic changes: Chosack et al, 23 Felippe et al, 28 Steiner et al, 29 Chawla et al 33 and Túrkún. 36 The study conducted by Chawla 33 found mineralized tissue formation after intracanal dressing remained in the root canal for 6 to 12 months without periodic changes.…”
Section: Discussionsupporting
confidence: 81%
“…Felippe et al 28 reported infeasible carrying out several changes of calcium hydroxide paste in teeth with incomplete root formation and infected root canal system. The present study corroborates the authors while disagreeing with Holland et al, 38 Holland et al, 39 Hulsmann, 40 Holland et al 41 and Nedley and Powers 42 who believe that root canal disinfection as well as mineral tissue deposition stimulating root apex closure rely on the alternate use of calcium hydroxide paste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a complete apical development was observed without paste replacement after 15 months. Felippe et al (32), in a study conducted in dogs, observed that the formation of apical calcified tissue was more noticeable in the root canals when the paste had not been renewed. Even though the frequent changes of calcium hydroxide pastes significantly reduced the intensity of the inflammatory process, the authors suggested that the dressing should only be changed when the sealing had failed or when there is a flare-up.…”
Section: Discussionmentioning
confidence: 98%
“…A utilização do hidróxido de cálcio, apesar das suas excelentes propriedades biológicas, apresenta algumas desvantagens como: tempo de tratamento prolongado (34, 37), necessidade de trocas (34,38,39) e enfraquecimento da estrutura dentária quando utilizado por um longo período de tempo (40)(41)(42)(43).…”
Section: Análise Estatísticaunclassified